Ultrasonic system for noninvasive measurement of hemodynamic parameters of human arterial-vascular system - POWAŁOWSKI, Tadeusz (Archives of Acoustics, 1988)
This paper presents the working principle of an ultrasonic system constructed for the simultaneous noninvasive measurement of the blood flow velocity and, the diameter of the blood vessel. A bi-directional c.w. Doppler flowmeter was used to measure the blood flow velocity. The echo method was used to measure the blood vessel diameter and its changes. The values of the parameters measured were transfered to the computer connected on line with the ultrasonic measuring system. A programme was elaborated for computer analysis of a number of hemodynamic parameters determined from the measured blood flow velocity and the instantaneous diameter of a blood vessel. They are the blood flow rate, the blood pressure, the vascular input impedance and the elasticity of arterial vessel walls. Connected to a computer, the ultrasonic measuring system was used in examinations of the carotid arteries.